A note on modeling of tumor regression for estimation of radiobiological parameters. Issue 8 (30th November 2016) - Zhong, Hualiang; Chetty, Indrin
Abstract : Purpose: Accurate calculation of radiobiological parameters is crucial to predicting radiation treatment response. Modeling differences may have a significant impact on derived parameters. In this study, the authors have integrated two existing models with kinetic differential equations to formulate a new tumor regression model for estimation of radiobiological parameters for individual patients. Methods: A system of differential equations that characterizes the birth‐and‐death process of tumor cells in radiation treatment was analytically solved. The solution of this system was used to construct an iterative model (Z‐model). The model consists of three parameters: tumor doubling time Td, half‐life of dead cells Tr, and cell survival fraction SFD under dose D. The Jacobian determinant of this model was proposed as a constraint to optimize the three parameters for six head and neck cancer patients. The derived parameters were compared with those generated from the two existing models: Chvetsov's model (C‐model) and Lim's model (L‐model). The C‐model and L‐model were optimized with the parameter Td fixed. Results: With the Jacobian‐constrained Z‐model, the mean of the optimized cell survival fractions is 0.43 ± 0.08, and the half‐life of dead cells averaged over the six patients is 17.5 ± 3.2 days. The parameters Tr and SFD optimized with the Z‐model differ by 1.2% and 20.3% from those optimized with the Td ‐fixed C‐model, and by 32.1% and 112.3% from those optimized with the Td ‐fixed L‐model, respectively. Conclusions: The Z‐model was analytically constructed from the differential equations of cell populations that describe changes in the number of different tumor cells during the course of radiation treatment. The Jacobian constraints were proposed to optimize the three radiobiological parameters. The generated model and its optimization method may help develop high‐quality treatment regimens for individual patients.